On the exponential decay for viscoelastic mixtures - Passarella, F.; Zampoli, V. (Archives of Mechanics, 2007)
This paper concerns the study of mixtures composed of a thermoelastic solid and a viscous fluid. For these mixtures, the dissipation effects are connected with the viscosity rate of one constituent and with the relative velocity vector. Using the time-weighted surface power method, associated with the linear process, we obtain some spatial decay estimates, characterized by time-independent and time-dependent decay rates, respectively. The first type of estimate is appropriate for large values of time, while the other is useful for short values of the same variable.